2017
DOI: 10.3389/fphar.2017.00858
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptors As Drug Targets for Treatment of Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a clinical condition characterized by pulmonary arterial remodeling and vasoconstriction, which promote chronic vessel obstruction and elevation of pulmonary vascular resistance. Long-term right ventricular (RV) overload leads to RV dysfunction and failure, which are the main determinants of life expectancy in PAH subjects. Therapeutic options for PAH remain limited, despite the introduction of prostacyclin analogs, endothelin receptor antagonists, phosphodiesterase typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 222 publications
(299 reference statements)
0
28
0
Order By: Relevance
“…P2YRs belong to the δ-branch of class A G-protein-coupled receptor (GPCR) family and contain seven hydrophobic transmembrane regions connected by three extracellular loops and three intracellular loops ( 3 ). Based on the phylogenetic and structural divergence, two distinct P2YR subgroups have been identified ( 23 ). The first group contains P2Y 1/2/4/6/11 Rs, with a sequence homology of 35–52% in amino-acid composition and the presence of a Y–Q/K–X–X–R defining motif in the transmembrane α-helix 7.…”
Section: Purinergic Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…P2YRs belong to the δ-branch of class A G-protein-coupled receptor (GPCR) family and contain seven hydrophobic transmembrane regions connected by three extracellular loops and three intracellular loops ( 3 ). Based on the phylogenetic and structural divergence, two distinct P2YR subgroups have been identified ( 23 ). The first group contains P2Y 1/2/4/6/11 Rs, with a sequence homology of 35–52% in amino-acid composition and the presence of a Y–Q/K–X–X–R defining motif in the transmembrane α-helix 7.…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…The second group contains P2Y 12/13/14 Rs, with a sequence homology of 47–48% and the presence of the K–E–X–X–L motif in transmembrane α-helix 7. Moreover, the two subgroups also differ in their primary coupling to G-proteins ( 23 ). P2Y 1/2/4/6/11 Rs primarily couple to G q /G 11 and initiate phospholipase C/inositol trisphosphate/diacylglycerol pathway to increase intracellular calcium, whereas P2Y 12/13/14 Rs principally couple to G i/0 and inhibit adenylate cyclase (AC) to decrease intracellular cyclic AMP (cAMP).…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…PHT is the most serious complication of ASD and the most significant cause of early mortality and reduced functional capacity in these patients (10,11). Previous studies showed that patients with PHT had endothelial dysfunction independent of its cause (12,13). In view of this, we considered that PHT would develop, and thus PWV might be elevated in patients with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results demonstrated the therapeutic potential of abrogation of ADORA2B signaling in lung injury and PH; however, it was not known whether vascular ADORA2B could contribute directly to the development of PH in an in vivo setting. Similarly, the role of ADORA2B in clinical or experimental models of PAH had not been addressed until now (Alencar et al, 2017 ). Strikingly, our results show that switching-off vascular smooth muscle ADORA2B is able to prevent HX-SU and BLM induced PH without altering fibrotic deposition levels in BLM-exposed mice.…”
Section: Discussionmentioning
confidence: 99%